'Flexible and Imaginative': The EU's Accommodation of Northern Ireland in the UK–EU Withdrawal Agreement. (April 2021) - Hayward, Katy
The 1998 Good Friday (Belfast) Agreement that cemented the peace process formalized Northern Ireland's position as a region integrally connected to both Great Britain and the Republic of Ireland. The multilevel governance and cross-border cooperation this entailed was enabled by common UK and Irish membership of the European Union. The UK's decision to leave the EU posed risks to this settlement. In response, they engaged in a quest for 'flexible and imaginative solutions' to this conundrum. The unique arrangements established through the Protocol on Ireland/Northern Ireland in the UK–EU Withdrawal Agreement (2019) mark an innovative and ambitious development for the EU. First, it de facto includes a region of a non-member state within its internal market for goods and, second, it delegates the enforcement of its rules to that non-member state. The Protocol represents a significant departure for the EU in terms of its typical engagement with external actors. Most significantly, it will not only represent a 'live' concern for the EU but a unique type of responsibility.